Analysis of Rainwater Harvesting's Potential for Clean Water Savings, Energy Efficiency and Carbon Emission Reduction at SDN Ragunan 08 Jakarta - Hendry Patabang Bara; Hans Dermawan; Andri Rachmanto Wibowo (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The increasing demand for clean water in educational facilities has led to greater groundwater exploitation, resulting in higher energy consumption for pumping and increased carbon emissions. Rainwater Harvesting (RWH) offers an alternative water source that supports sustainable development and Net Zero Carbon initiatives. This study evaluates the technical, environmental, and economic feasibility of implementing an RWH system at SDN Ragunan 08 Jakarta to meet non-potable water demands, particularly for toilet flushing. The analysis included water demand estimation, rainfall projection using Tropical Rainfall Measuring Mission (TRMM) satellite data validated through statistical methods, assessment of energy savings and carbon emission reductions, and economic evaluation using the Life Cycle Cost (LCC) approach. The results showed that the school’s non-potable water demand was 9,492 liters/day (9.49 m³/day). Validation of TRMM data using logarithmic regression produced a very strong correlation (R = 0.998), indicating high reliability for rainfall estimation. With a reservoir capacity of 60 m³, the RWH system could reduce groundwater use by up to 56.7% during the driest month and fully meet water demand in several rainy months. Reduced groundwater pumping lowered annual carbon emissions from 2,904.55 kg CO₂ to 968.18 kg CO₂. Economically, the system requires an initial investment of IDR 74,741,413.97 and has a 10-year LCC of IDR 93,777,649.02. Although further optimization is needed to improve economic feasibility, the RWH system demonstrates strong potential as a sustainable water management strategy through groundwater conservation, energy savings, and carbon emission reduction.